FOR THE CONTROL OF ENVIRONMENTAL CHANGES IN THE COASTAL STRIP CASE OF THE FRINGE BETWEEN THE MENCHA AND NIL RIVERS (EAST OF THE WILAYA OF JIJEL-ALGERIA) - Bougassa Abdelhafid (International Journal of Innovative Technologies in Social Science, 2024)
Environmental issues have constantly constituted the main focus of the Algerian authorities in the development of different sectors of activity. The challenge of reconciling economic growth with the protection of the environment and coastal areas dates back to the early 1980s. It is clearly expressed through a range of regulatory texts and anticipatory and restrictive territorial planning guidelines.The coastal strip between Mencha and Nil rivers to the east of the wilaya of Jijel has not been excluded from strategies for controlling natural resources and territorial projects (PAW, PDAU, and PAC). The anthropization of this small territory gives food for thought on the conditions for controlling the environmental impacts induced by overcrowding, rampant urbanization, landscape fragmentation, pollution and the reduction of natural spaces. Through this article, we aim to assess the socio-economic impacts on the study territory on the one hand and the factors and prospects of the possible divide between the state of affairs and the principles of good land and environmental governance.(The word Oued is a local name. It is used to mean river in this article).